Mortality change, the uncertainty effect, and retirement - Sebnem Kalemli-Ozcan; David N. Weil (Brown University, Department of Economics, 2001)
We examine the role of declining mortality in explaining the rise of retirement over the course of the 20th century. We construct a model in which individuals make labor/leisure choices over their lifetimes subject to uncertainty about their date of death. In an environment in which mortality is high, an individual who saved up for retirement would face a high risk of dying before he could enjoy his planned leisure. In this case, the optimal plan is for people to work until they die. As mortality falls, however, it becomes optimal to plan, and save for, retirement. We simulate our model using actual changes in the US life table over the last century, and show that this “uncertainty effect” of declining mortality would have more than outweighed the “horizon effect” by which rising life expectancy would have led to later retirement. A calibration exercise, allowing for heterogeneity in tastes and other non-mortality factors influencing retirement, shows that falling mortality plausibly had a quantitatively significant effect on retirement.
Keywords: E21; I12; J11; J26; 330; Sterblichkeit; Alterssicherung; Altersgrenze; Lebenszyklus; Theorie